1970
DOI: 10.1007/bf00564289
|View full text |Cite
|
Sign up to set email alerts
|

Alkaloids ofStephania hernandifolia

Abstract: From the herb Stephania hernandifolia (family Menispermaceae) growing in Transcaucasia, via its sparingly soluble hydrochloride, we have isolated a base with the composition C20H27OsN , mp 114-115 ° C (from ether), 144.5 ° C (from methanol), [aiD --97"9° (c 0.7, ethanol), mol wt 370 (Rast); hydrochloride with mp 199.5-200.5 ° C (from ethanol). It contains three OCH 3 groups (signals in the NMR spectrum at 3.38, 3.47, and 3.65 ppm), two OH groups (3300 and 3520 cm -~) and an NCH~ group (signal at 2.46 ppm). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1970
1970
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Confirmation for the earlier structural proposal for flavin-antine84,85 was obtained by the synthesis of (±)-flavinantine (76). Diazotization of the aminotetraisoquinoline 77 followed by thermal decomposition produced 78 In a similar manner to the synthesis of flavinantine, diazotization of 6 '-aminolaudanosine (81) at 0-5°followed by an increase of the temperature to 70°for 1 hr produced O-methylflavinantine (82) (1.4% yield) as well as (±)-glaucine ( 83) and (±)-landanosine (84). Compound 85 was also converted to (±)-0-methylfiavinantine using identical conditions.…”
Section: (±)-Flavinantine (3-hydroxy-26dimethoxymorphinandienoné)mentioning
confidence: 87%
See 1 more Smart Citation
“…Confirmation for the earlier structural proposal for flavin-antine84,85 was obtained by the synthesis of (±)-flavinantine (76). Diazotization of the aminotetraisoquinoline 77 followed by thermal decomposition produced 78 In a similar manner to the synthesis of flavinantine, diazotization of 6 '-aminolaudanosine (81) at 0-5°followed by an increase of the temperature to 70°for 1 hr produced O-methylflavinantine (82) (1.4% yield) as well as (±)-glaucine ( 83) and (±)-landanosine (84). Compound 85 was also converted to (±)-0-methylfiavinantine using identical conditions.…”
Section: (±)-Flavinantine (3-hydroxy-26dimethoxymorphinandienoné)mentioning
confidence: 87%
“…The alkaloid delavaine, mp 149-150°, [a]o -240°, has been isolated from Stephania delavayi, and the dihydromorphinandienone structure 167 or 168 has been proposed. 84 have shown that 50% of the activity was located in the alkaloid fraction. From tic and glc, this was shown to contain norcodeine (161), codeine (132), and normorphine (162).8 2 It seems very likely that a morphinandienone intermediate like compound 160 plays an important role in this biological transformation and an evaluation of the biological activity of such a morphinandienone has some merit.…”
Section: Formation Of Flavinantine Flavinine Amurine Nadurine and Pal...mentioning
confidence: 99%
“…A comparison of the composition and constants of the described alkaloid with the product from the reduction of hernandoline with sodium borohydride [1], and also the formation of identical products by Hofmann degradation show that the structures of the substances are similar.…”
mentioning
confidence: 88%
“…EtOH UV spectrum: Xma x 216 and 285 n~ (log e 3.94 and 3.48). This alkaloid has not been described in the literature and is new.The Hofmann degradation of the alkaloid yielded a methiodide with mp 178-180 ° C and a desbase with mp 114-115 ° C giving no depression of the melting point in admixture with the desbase of hernandoline [1]; the two substances gave spots with the same Rf value in TLC on alumina in an ether-methanol (25 : 168) system.On acetolysis, the desbase formed a substance with mp 163-164 ° C identical with the diacetoxydimethoxyphenantrene obtained from hernandoline [1].…”
mentioning
confidence: 95%
See 1 more Smart Citation